The lizard genera anadia and ptychoglossus in colombia (1944)
Study of the available Colombian material of these genera necessitates the description of a new Anadia, the transference of a species described as an Anadia to the related genus Ptychoglossus, and affords a definite locality in Colombia for the type species of Anadia, hitherto known only from "Tropical America??". Anadia and Ptychoglossus agree in having the scales in transverse rings, the ventrals continuous with, rather than separated from, the laterals and dorsals, and in having prefrontal plates. They differ in that Anadia has squarish, flat dorsals, while in Ptychoglossus they are narrow, elongate, and more or less keeled. In neither genus are the dorsals separated from the ventrals by smaller scales, as they are in Euspondylus, nor is there an oblique arrangement of the laterals, as there is in Pantodactylus. In Anadia the dorsals of one ring may follow those of the next or they may alternate with them (or some follow and some alternate), whereas in Ptychoglossus the alternation is regular.